DIAGNOSIS OF STUDENTS' METACOGNITIVE SKILLS VIEWED FROM REVIEW ASPECT IN CLASS VIII INTEGRATED ISLAMIC SMP SULTHONIYAH SAMBAS - Mutazam Mutazam (CV. ADIBA AISHA AMIRA, 2023)
This study aims to determine the level of metacognitive abilities of SMP IT Sulthoniyah Sambas students. The type of research in this research is descriptive research with a qualitative approach. The use of metacognitive strategies in solving mathematical problems will lead students to understand and control their thinking processes, analyze, be objective, careful and logical in solving the mathematical problems they are facing. The research was conducted in class VIII SMP IT Sulthoniyah Sambas, which consisted of 34 students using a questionnaire method, test questions and supplemented by interviews. Based on the results of the study, it was shown that the students' metacognitive skills from the review (re-checking aspect) got student responses at an average percentage of 63%, thus the metacognitive skills of SMP IT Sulthoniyah Sambas students were still quite sufficient